(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction: Facial growth pattern is an important factor in planning orthodontic treatment properly. Knowledge of arch forms is important for an orthodontist, as it is related to future treatment outcome. Factors such as age, sex, and ethnicity are also important. The purpose of present study was to evaluate the dental arch dimensions in a different facial pattern in regional population, to evaluate correlation in the facial pattern with dental arch width to evaluate the differences in dental arch width between male and female subjects. Materials: The present study was conducted on 120 untreated subjects comprising of 60 males and 60 females aged between 16 to 38 years. The Jarabak’s ratio (posterior facial height/anterior facial height) was measured on cephalograms of each patient. Maxillary and mandibular inter-canine, first inter-premolar, second inter-premolar and first inter-molar widths were measured on study models of each patient. Results: There was no significant correlation between dental arch width and vertical facial pattern in regional population. In males, arch width is greater in canine, premolar and molar region than females. Conclusion: It was concluded that dental arch width is not associated with the vertical facial pattern but it is associated with gender. Thus, using individualized arch wires according to gender is suggested during orthodontic treatment. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S26-S31